Molecular Engineering of Efficient Singlet Oxygen Generators with Near‐Infrared AIE Features for Mitochondrial Targeted Photodynamic Therapy. (25th June 2021) - Yuan, Gang; Lv, Cheng; Liang, Jichao; Zhong, Xinxin; Li, Yuan; He, Jiacun; Zhao, Anjing; Li, Li; Shao, Yuanhe; Zhang, Xiuhua; Wang, Shengfu; Cheng, Yu; et al.
Abstract: Aggregation‐caused fluorescence quenching with insufficient production of reactive oxygen species (ROS) has limited the application of photosensitizers (PSs) in fluorescence‐imaging‐guided photodynamic therapy (PDT). Aggregation‐induced emission PSs (AIE‐PSs) exhibit enhanced fluorescence intensity and a high efficiency of ROS generation in the aggregation state, which provides an opportunity to solve the above problems. Herein, a series of AIE‐PSs are successfully designed and synthesized by adjusting the D–A intensity through molecular engineering. The photophysical properties and theoretical calculations prove that the synergistic effect of 3, 4‐ethylenedioxythiophene and quinolinium increases the intramolecular charge transfer effect (ICT) of the whole molecule and promotes the intersystem crossing (ISC) from the lowest excited singlet state (S1 ) to the lowest triplet state (T1 ). Among these AIE‐PSs, the optimal AIE‐PS (TPA‐DT‐Qy) exhibits the highest generation yield of 1 O2 (5.3‐fold of Rose Bengal). Further PDT experiments show that the TPA‐DT‐Qy has a highly efficient photodynamic ablation of breast cancer cells (MCF‐7 and MDA‐MB‐231) under white light irradiation. Moreover, the photodynamic antibacterial study indicates that TPA‐DT‐Qy has the discrimination and excellent photodynamic inactivation of S. aureus . This work provides a feasible strategy for the molecular engineering of novel AIE‐PSs to improve the development of fluorescence‐imaging‐guided PDT. Abstract : A series of aggregation‐induced emission‐photosensitizers (AIE‐PSs) are designed and synthesized successfully to achieve photosensitizers with excellent properties containing AIE‐active, high 1 O2 generation, NIR emission, mitochondrial targeting. The introductions of triphenylamine, 3, 4‐ethylenedioxythiophene, and quinolinium blocks do these AIE‐PSs work, which are appropriate for fluorescence‐imaging‐guided photodynamic therapy. Typically, TPA‐DT‐Qy exhibits efficient photodynamic anticancer and antibacterial.